Pengaruh Kepemilikan Asing Dan Tunneling Incentive Terhadap Tax Avoidance Dengan Profitabilitas Sebagai Variabel Moderasi (Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2017-2021 - Novena OpraVita (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study aims to determine the effect of foreign ownership and Tunnelling Incentives on Tax Avoidance with profitability as a moderating variable. The population of this study are manufacturing companies listed on the Indonesian stock exchange. The sample in this study was determined based on the manufacturing companies listed on the Indonesian stock exchange during the period 2017-2021, companies that do not issue financial reports consecutively during the 2017-2021 period, financial statements using foreign currencies, companies that do not earn consecutive profits during the 2017-2021 period. The results show that foreign ownership has no effect on Tax Avoidance, Tunneling Incentives have an effect on tax avouidance,profitability strengthens the relationship between foreign ownership and Tax Avoidance, profitability weakens the relationship between Tunneling Incentives and Tax Avoidance.